Anisometropic Amblyopia: Analysis of Treatment Results with Patching of Dominant Eye and Refraction with Active Visual Therapy (AVT) in School Age Children - Mohammad Aamir Khan, Fawad Ahmad, Shamsullah Bazai, Muhammad Aamir Shahzad, Muhammad Sohail Arshad, Shahid Nazeer (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to conduct an analysis of the effectiveness of treating school-aged children by patching the eye that is considered to be dominant and performing refraction using active visual therapy (AVT). Place of study: Jinah international hospital abbottabad Duration of study: October 2021 to April 2022 Methods: There were 65 children with ages 6-16 years had anisometropic amblyopia included in this study. After informed written agreement, participants’ demographics were recorded. Posterior and back anterior segments were checked. Recorded best visual therapy. Refractive error of amblyopic eyes was +7 to -5 diopters. Refraction was corrected. Improvement in visual acuity and refraction were assessed every two months. Post-treatment visual acuity of 6/24, 6/36, 6/60 was tested with a regression and correlation T-test. SPSS 21.0 analyzed all data. Results: Among 65 children, 40 (61.5%) were males and 25 (38.5%) were females. Mean age of the patients was 8.7±4.17 years. Hypermetropia was the most common refractive error found in 45 (69.2%) cases followed by myopia in 20 (30.8%) cases. Pre-treatment 24 (36.9%) patients had BCVA 6/24, 12 (18.5%) patients had 6/36, 17 (26.2%) patients had 6/60 and 12 (18.5%) had CF. Post-treatment 18 (27.7%) had BCVA 6/6, 10 (15.4%) had 6/9, 11 (16.9%) cases had 6/12, 12 (18.5%) children had 6/18, 5 (7.7%) had 6/24, 6 (9.2%) had BCVA 6/60 and 3 (4.6%) had CF. Conclusion: In this study, we came to the conclusion that the treatment for anisometropic amblyopia, which involves the patching of the patient’s dominant eye and the refraction of the amblyopic eye using active visual therapy, is beneficial.